(untitled) (Informatica, 2021)
Information Technologies have come to be accepted as the new normal in many parts of the world. Events like the outbreak of the COVID-19 have highlighted the significance of these artifacts in facilitating the continuance of or daily activities without grinding to a halt. While some educational institutions, from the kindergarten all through to higher education, were actively engaged in teaching and learning, others were grappling with implementation issues. This paper takes a look at Computer-Mediated Communication (CMC) Portal implementation in HEIs within a developing country through the lens of Giddens’s Structuration Theory. Two Ghanaian HEIs’ implementation of CMC portals is examined using Tetteh et al’s CMC portal implementation framework as well as a structuration theory adapted by Orlikowski & Robey from Giddens’s work. Findings reveal an indistinct and almost absent consideration of the broader institutional goals for implementing CMC portals. It was also found that the activities involved in the adoption, implementation, and institutionalization of technology into institutional processes, are often not adequately considered, were unaligned with institutional visions, and not well understood. Strategies that can improve the utilization of CMC portal initiatives and guide implementation efforts of HEIs in Ghana are then advanced. Additionally, the study broadens our understanding of the structuration perspective on the outcomes of technology implementation in institutions providing another lens for identifying the underlying causational factors.